Development of short pulse Erbium-Ytterbium and Thulium-Ytterbium Co-doped cladding pumped fiber lasers / Ibrahim Muhammad Babar - Ibrahim , Muhammad Babar (2017)
This research work focuses on the development of fiber lasers operating in both continuous wave (CW) and short pulse modes by using two differentYtterbium co-doped double-clad fibers; Erbium-Ytterbium co-doped fiber (EYDF) and Thulium-Ytterbium co-doped fiber (TYDF) as a gain medium. Both fibers are characterized in both linear and ring cavity configurations by using cladding pumping technique with different fiber lengths. In linear configuration, the EYDF laser operates at 1545.6 nm with slope efficiency of 18.4% at the optimum length of 5m. With the ring configuration, the EYDFL operates at lower efficiency of 4.6%. The TYDF laser (TYDFL) achieves the maximum slope efficiency of 0.88% operating at 1961.4 nm when the gain medium is fixed at 10 m. A multi-wavelength TYDFL operating at 2 μm region is also demonstrated based on nonlinear polarization rotation (NPR) effect. The laser generated triple-wavelength outputs at 1982.12 nm, 1986.69 nm and 1991.26 nm. Q-switched EYDFL is demonstrated by employing Molybdenum disulfide (MoS2) polyvinyl alcohol (PVA) film as saturable absorber (SA). The laser operates at around 1563 nm with repetition rate in the range of 6.4 kHz to 113.4 kHz as the pump power is varied from 100 to 1250 mW. Q-switched TYDFL is demonstrated by utilizing multi-walled carbon nanotubes PVA film as SA. The laser operates at 1977.5 nm with pulse repetition rate from 18.8 to 50.6 kHz, and corresponding pulse width from 8.6 to 1.0 μs, by varying the pump power from 1591.3 to 2261.5 mW. Finally, EYDFL and TYDFL operating in mode-locking mode are demonstrated by using a graphene PVA film based SA. The EYDFL operates at about 1562.5 nm with repetition rate of 0.92 MHz and pulse width of 387 ns. The mode-locked TYDFL operates around 1942.95 nm with repetition rate of 11.76 MHz when the fiber is pumped from 1487 to 1964 mW. The EYDF and TYDF lasers operate in eye-safe regions of 1.5 and 2 μm, respectively and thus they find potential applications in optical communication, spectroscopy, material processing, metrology and medicine.